Mentoring Experiences and Perceptions of Latino Male Faculty in Higher Education. Issue 1 (February 2020) - Salinas, Cristobal; Riley, Patrick; Camacho, Lazaro; Floyd, Deborah L.
While some higher education institutions attempt to help support and retain Latino students until graduation, these same institutions often neglect the experiences of Latino faculty members. The main challenges Latino faculties encounter in higher education include cultural taxation, discrimination, and feelings of isolation. Research is limited on the experiences and role of mentorship for Latino male faculty. This phenomenological study examines how Latino male faculty members in higher education perceive mentoring both as a mentee and as a mentor. This study also examines the impact of mentoring on professional development and the path of Latino male faculty. Findings illustrate that family values, mentoring in higher education, and desire to pay forward the mentoring experience are factors that impact Latino male faculty perception of mentorship.